Prevalence of Carbapenem-resistant Klebsiella pneumoniae in vegetable and water samples in Dhaka South - Raymond, Mugenyi; Precious, Bisoboka Claire; Haque, Ashrin; Rahman, Mohammad Mushfiqur (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.